Another level of complex-ity: The role of metabolic channeling and metabolons in plant terpenoid metabolism - Gutensohn, Michael; Hartzell, Erin; Dudareva, Natalia (Frontiers in Plant Science, 2022)
Terpenoids constitute one of the largest and most diverse classes of plant metabolites. While some terpenoids are involved in essential plant processes such as photosynthesis, respiration, growth, and development, others are specialized metabolites playing roles in the interaction of plants with their biotic and abiotic environment. Due to the distinct functions and properties of specific terpenoid compounds, there is a growing interest to introduce or modify their production in plants by metabolic engineering for agricultural, pharmaceutical, or industrial applications. The MVA and MEP pathways and the prenyltransferases providing the general precursors for terpenoid formation, as well as the enzymes of the various downstream metabolic pathways leading to the formation of different groups of terpenoid compounds have been characterized in detail in plants. In contrast, the molecular mechanisms directing the metabolic flux of precursors specifically towards one of several potentially competing terpenoid biosynthetic pathways are still not well understood. The formation of metabolons, multi-protein complexes composed of enzymes catalyzing sequential reactions of a metabolic pathway, provides a promising concept to explain the metabolic channeling that appears to occur in the complex terpenoid biosynthetic network of plants. Here we provide an overview about examples of potential metabolons involved in plant terpenoid metabolism that have been recently characterized and the first attempts to utilize metabolic channeling in terpenoid metabolic engineering. In addition, we discuss the gaps in our current knowledge and in consequence the need for future basic and applied research.